2017
DOI: 10.18632/oncotarget.14829
|View full text |Cite
|
Sign up to set email alerts
|

The HDAC inhibitor AR42 interacts with pazopanib to kill trametinib/dabrafenib-resistant melanoma cells in vitro and in vivo

Abstract: Studies focused on the killing of activated B-RAF melanoma cells by the histone deacetylase (HDAC) inhibitor AR42. Compared to other tumor cell lines, PDX melanoma isolates were significantly more sensitive to AR42-induced killing. AR42 and the multi-kinase inhibitor pazopanib interacted to activate: an eIF2α–Beclin1 pathway causing autophagosome formation; an eIF2α–DR4/DR5/CD95 pathway; and an eIF2α-dependent reduction in the expression of c-FLIP-s, MCL-1 and BCL-XL. AR42 did not alter basal chaperone activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 45 publications
5
87
1
Order By: Relevance
“…The levels of CCL2 did not alter and those of CCL5 declined; the levels of the chemokines CCL2 and CCL5 were increased which would predict for macrophage invasion and activation. 16 In recent melanoma studies, in the plasma from animals exposed to [HDAC inhibitor + anti-PD-1], HDAC exposure also increased the levels of IL-12 and reduced the levels of IL-10, TGFβ and IL-1α, again in agreement with the presence of M1, but not M2, macrophages in the tumor. And as we have observed in our present pancreatic cancer work, the cytokine data from HDAC inhibitor plus anti-PD-1 exposed melanoma tumors correlated with increased activated T cell, M1 macrophage, neutrophil and NK cell infiltration.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The levels of CCL2 did not alter and those of CCL5 declined; the levels of the chemokines CCL2 and CCL5 were increased which would predict for macrophage invasion and activation. 16 In recent melanoma studies, in the plasma from animals exposed to [HDAC inhibitor + anti-PD-1], HDAC exposure also increased the levels of IL-12 and reduced the levels of IL-10, TGFβ and IL-1α, again in agreement with the presence of M1, but not M2, macrophages in the tumor. And as we have observed in our present pancreatic cancer work, the cytokine data from HDAC inhibitor plus anti-PD-1 exposed melanoma tumors correlated with increased activated T cell, M1 macrophage, neutrophil and NK cell infiltration.…”
Section: Discussionmentioning
confidence: 58%
“…PD-L1, MHCA, ODC and IDO-1. [16][17][18][19] Our prior studies with sorafenib and vorinostat in hepatoma cells had argued that the drug-induced formation of autophagosomes was partially protective against drug combination lethality. However, the role of autophagy regulating cell survival in pancreatic cancer cells expressing mutated K-RAS proteins is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recent prior studies from our group have demonstrated how the PDE5 inhibitor sildenafil (Viagra) can enhance the DNA damage response activation of ATM by pemetrexed or an HDAC inhibitor. 19,20 Sildenafil causes the tumor cells to generate nitric oxide, which reacts with tumor cell ROS to elevate the levels of peroxy-nitrate. Peroxy-nitrate is a potent inhibitor of protein phosphatases that inactivate ATM and PERK/eIF2α, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific rationale for the use of HDAC inhibitors (HDACi) or DNA methyltransferase inhibitors (DNMTi) in ongoing clinical trials in cancer patients relies on the ability of these drugs to inhibit tumor cell growth and to induce cell differentiation [107]. However, DNMTi and HDACi are also capable of upregulating the expression of TAAs in different solid tumors [108][109][110][111], thus potentially sensitizing cancer cells to ICIs by upregulating CTLA4, PD-1, PD-L1, and PD- Taken together, published data indicate that bulk tumor cells and CSCs may exploit epigenetic repression of specific immune genes to escape killing by immune cells. It is likely that the interplay between genetic and epigenetic modifications affects the carcinogenesis process and takes part in the selective pressures involved in immune cell escape.…”
Section: Epigenetic Control Of Stemness Features and Immune Escapementioning
confidence: 99%
“…The scientific rationale for the use of HDAC inhibitors (HDACi) or DNA methyltransferase inhibitors (DNMTi) in ongoing clinical trials in cancer patients relies on the ability of of 15 these drugs to inhibit tumor cell growth and to induce cell differentiation [107]. However, DNMTi and HDACi are also capable of upregulating the expression of TAAs in different solid tumors [108][109][110][111], thus potentially sensitizing cancer cells to ICIs by upregulating CTLA4, PD-1, PD-L1, and PD-L2 molecules on both tumor cells and TILs [112,113]. HDACi can also restore the expression of MHC class I and II molecules, which are downregulated as a result of transcriptional alterations in the IFNγ and NF-kB (for MHC class I) or the CIITA (for MHC class II) pathways [108], thus facilitating innate and adaptive antitumor immune responses.…”
Section: Epigenetic Control Of Stemness Features and Immune Escapementioning
confidence: 99%